The Mammalian Diving Response: Inroads to Its Neural Control - Panneton, W. Michael; Gan, Qi (Frontiers in Neuroscience, 2020)
The mammalian diving response is a remarkable behavior first formally studied by Laurence Irving and Per Scholander in the late 1930’s. The diving response is called such because it is most prominent in marine mammals such as seals, whales, and dolphins, but nevertheless is found in all mammals studied. It consists generally of breathing cessation (apnea), a dramatic slowing of heart rate (bradycardia), and an increase in peripheral vasoconstriction. The diving response is thought to conserve vital oxygen stores and thus maintain life by directing perfusion to the two organs most essential for life, the heart and the brain. The diving response is important, not only for its dramatic power over autonomic function, but also because it alters normal homeostatic reflexes such as the baroreceptor reflex and respiratory chemoreceptor reflex. The neurons driving the reflex circuits for the diving response are contained within the medulla and spinal cord since the response remains after brainstem transection at the pontomedullary junction. Neuroanatomical and physiological data are reviewed suggesting brainstem areas important for the apnea, bradycardia and peripheral vasoconstriction induced by underwater submersion. Defining the brainstem circuit for the diving response may open broad avenues for understanding the mechanisms of suprabulbar control of autonomic function in general, as well as implicate its role in some clinical states. Knowledge of the proposed diving circuit should facilitate studies on elite human divers performing breath-hold dives as well as investigations on Sudden Infant Death Syndrome (SIDS), stroke, migraine headache and arrhythmias. We have speculated that the diving response is the most powerful autonomic reflex known.